Shipwrecks of sussex - Hughes, Wendy ([S.l.] : The History Press, 2011)
The Sussex coastline can boast to be one of the most wreck-rich regions in the English Channel. In fact there are over 4,000 recorded wrecks along the coast. Over the years many ships that have sailed along the Sussex coast have run aground owing to the fierce currents and shallow sand banks, as treacherous seas appear from nowhere when the tide or the weather changes. Revealing the events behind many of the shipwrecks that have occurred along the Sussex coastline, this book features a wealth of fascinating stories, from the Indiana$1 (Bs cargo of oranges and lemons that covered the beach and were retrieved by hungry locals to ships torpedoed by acts of war, and the recent wreck of the Ice Prince that spectacularly deposited many tons of timber upon Worthing beach in January 2008. With personal accounts and many old engravings and photographs, this book will fascinate locals and enthusiasts alike.s
Keywords: England--Sussex; Shipwrecks